Method for estimating condition of commutation of traction electric DC motors of carrier dumping during operation - V. V. Kharlamov; S. N. Nayden; P. K. Shkodun; P. G. Petrov; A. S. Khloptsov (Омский научный вестник)
The article describes a method for assessing the state of commutation of traction DC electric motors of BELAZ dump trucks based on processing data obtained using an automated video measuring commutation complex. The developed algorithm for the formation of the spark intensity value from the video image is given, the criteria for evaluating the switching are determined, the analysis of the modes and quality of operation of the traction electric motors is performed depending on the operating mode of the mining truck. The input and output data processing is carried out in the MATLAB 2017 program.